Acute kidney injury in dogs and cats 2. Management, treatment and outcome. Issue 6 (17th June 2013) - Li, Ronald; Mugford, Adam; Humm, Karen
Abstract : Acute kidney injury (AKI) is a commonly encountered emergency in small animal practice. Dogs and cats with AKI are mostly presented in the maintenance phase of the disease, by which point renal function has been severely compromised and clinical signs are apparent. The first article in this two‐part series, which was published in the May issue of In Practice discussed the pathogenesis and diagnosis of AKI. This article considers both specific therapy and general supportive treatment in dogs and cats.